Oro-gastro-intestinal digestion of starch in white bread, wheat-based and gluten-free pasta: Unveiling the contribution of human salivary α-amylase. (15th February 2019) - Freitas, Daniela; Le Feunteun, Steven
Highlights: We studied starch hydrolysis during dynamic in vitro digestions of bread and pasta. The contribution of salivary α-amylase (HSA) and pancreatic α-amylase was assessed. HSA released 30% (pasta) to 80% of starch (bread) during the gastric phase. >50% of the released starch was hydrolysed into oligosaccharides by HSA. Amylolysis by HSA is important and likely to influence the glycemic response. Abstract: Starch is a major determinant of the glycemic responses elicited by our diets, but the exact contribution of the two main amylolytic enzymes (salivary and pancreatic α-amylases) remains a matter of debate. Our aim was to investigate the contribution of the oral, gastric and intestinal phases to the hydrolysis of starch in bread and pasta during dynamic in vitro digestions using DiDGI®. Before its inactivation by the low gastric pH, salivary α-amylase released about 80% of the starch in bread and 30% of that in pasta, hydrolysing over half of it into oligosaccharides. Accordingly, the contribution of pancreatic α-amylase during the intestinal phase was lower for bread than pasta. Our results are well correlated with in vivo data, and demonstrate the importance of salivary α-amylase during oro-gastric processing of starchy foods. This finding is discussed in relation with observations regarding salivary α-amylase from other fields of knowledge.